THE ANALYSIS OF DEPOSITIONAL ENVIRONMENT OF BUSUI COAL, EAST KALIMANTAN AND SATUI COAL, SOUTH KALIMANTAN - SIMANJUNTAK (NIM 12101053); Pembimbing: Dr. Ir. Komang Anggayana, M.S., RICKY
Coal has the qualities and charactheristics which are unique for each location. Many factors cause those differences, e.g. coal facies, depositional environment, plants as coal constituents and geological process such as structures. In this case, the coal depositional environment is determined based on Diesel (1986) and Calder (1991) parameters. The coal samples are taken from two locations: Busui coal of Miosen age Warukin formation, Pasir basin, East Kalimantan and Satui coal of Eosen age Tanjung formation, Asam–Asam basin, South Kalimantan. Coal samples from each location are taken by channel sampling. Every channel has been divided in three samples based on their genetic characteristics which are represented by the interval difference of cleat characteristics. The samples are observed petrographycally to determine the reflectant vitrinite and coal maceral composition (%). As the result, Busui A (average reflectant vitrinite Rv = 0,59%), Busui B (average Rv = 0,56%), Satui A (average Rv = 0,54%), Satui B (average Rv = 0,58%) and Satui C (average Rv = 0,57%) could be categorized into sub bituminous coal, while Busui C (average Rv = 0,61%) has the rank of high volatile bituminous (Australian Standard, 1986). Coal depositional environment of Busui and Satui coal based on Diesel and Calder parameters is lower–upper delta plain with peat type of bog–ombrotrophic and bog forest–ombrotrophic.